2012
DOI: 10.1002/jbm.a.34424
|View full text |Cite
|
Sign up to set email alerts
|

Increased in vivo stability and functional lifetime of an implantable glucose sensor through platinum catalysis

Abstract: Understanding and improving in vivo materials related to signal stability and preservation for active chemical sensor and biosensor transduction systems is critical in achieving implantable medical sensors for long-term in vivo applications. During human in vivo clinical testing of an implantable glucose sensor based on a glucose sensitive hydrogel, post-explant analysis showed that the boronate recognition element had been oxidized from the fluorescent indicator, causing a rapid loss of signal within hours af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 25 publications
0
30
0
Order By: Relevance
“…35,36 In patients with type 1 diabetes using insulin glargine, a randomized trial showed that prandial TI led to significantly lower fasting and 1-and 2-hour postprandial glucose values compared to prandial insulin lispro, with a lower hypoglycemia event rate. 37 Several other published clinical studies have further supported TI's safety and efficacy as a prandial insulin in type 1 diabetes 29,38,39 and type 2 diabetes. 29,40,41 At the time of the study TI was an investigational drug that was approved on June 27, 2014, as an ultra rapid-acting insulin for oral inhalation indicated for the treatment of adults with type 1 or type 2 diabetes mellitus in the US by the food and drug administration.…”
mentioning
confidence: 95%
“…35,36 In patients with type 1 diabetes using insulin glargine, a randomized trial showed that prandial TI led to significantly lower fasting and 1-and 2-hour postprandial glucose values compared to prandial insulin lispro, with a lower hypoglycemia event rate. 37 Several other published clinical studies have further supported TI's safety and efficacy as a prandial insulin in type 1 diabetes 29,38,39 and type 2 diabetes. 29,40,41 At the time of the study TI was an investigational drug that was approved on June 27, 2014, as an ultra rapid-acting insulin for oral inhalation indicated for the treatment of adults with type 1 or type 2 diabetes mellitus in the US by the food and drug administration.…”
mentioning
confidence: 95%
“…26 By contrast, the Senseonics CGM sensor detects glucose via a nonenzymatic, abiotic methodology that is not subject to degradation or to the stability limitations inherent to enzyme-based systems. 18 In addition, transcutaneous sensors of other CGMs protrude from the skin and do not allow for resolution of an acute inflammatory response, thereby limiting sensor accuracy and performance. The Senseonics sensor is fully inserted into the interstitial tissue, thus allowing the body to heal the insertion wound and resolve the acute inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Ex vivo chemical analysis performed after sensor removal showed loss of fluorescence due to chemical degradation of the indicator moieties, the mechanism of which has been previously described. 18 The daily calibration points enable the system to account for this loss of fluorescence in vivo with a real-time assessment of the indicators sensitivity to glucose variations. This assessment enables updates to the fluorescent baseline and the responsiveness corresponding to the chemical kinetics for the degradation mechanisms.…”
Section: Sensor Lifementioning
confidence: 99%
“…It is then detected by an amperometric biosensor. From [5] While ultra-miniaturisation combined with surface functionalisation with selected molecules can lead to biocompatible devices, the issues of energy autonomy, selfdiagnosis, remote control, and data transmission remain considerable challenges for the implementation of such systems.…”
Section: Smaller and Smaller Implants And Sensorsmentioning
confidence: 99%